Thick Photographic Descriptions: Another Way of Telling Danish Welfare Landscapes - Van Haeren, Kristen (Writingplace, 2021)
This paper explores how ‘nature’ – in the form of the landscapes of two housing estates in Copenhagen – was a central part of the vision of establishing a good life for every citizen: nature was being valued as an essential amenity and common ground for the creation of the new welfare vision for all. Through an analysis of, and engagement with, historical documents – as well as situated photographic modes of inquiry – this investigation into welfare landscapes focuses on the less-acknowledged but vital forces that shape the green outdoor areas of the housing estates, framing details to emphasize the specificity of place and depicting a landscape for living where humans were central. This way of working can offer insights into multifarious spatial grounds, diverse interpretations of green spaces, and the construction of humane living environments designed for access to nature – but also provide civic opportunities and affordances for gathering, play, community, privacy, personal development and the like – all within these welfare landscapes.